2016
DOI: 10.1039/c6ra05857d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2-loaded silicate-1 monoliths and their application for degradation rhodamine B

Abstract: TiO2-loaded silicate-1 monoliths, with TiO2 (Degussa P25) nanoparticles loaded in silicate-1 crystal, were directly synthesized by combining sol–gel method and hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…High surface area and porous nature enable it to use in different application such as adsorption, catalyst and fine chemical industrial applications (Yin et al 2020;Yang et al 2020). Jing et al (2016) fabricated TiO 2 -loaded silicalite-1 for degradation of rhodamine B. They reported that adsorbent dosage plays a key role in dye removal efficiency as they observed a significant increment in dye removal efficiency with adsorbent dosage.…”
Section: Introductionmentioning
confidence: 99%
“…High surface area and porous nature enable it to use in different application such as adsorption, catalyst and fine chemical industrial applications (Yin et al 2020;Yang et al 2020). Jing et al (2016) fabricated TiO 2 -loaded silicalite-1 for degradation of rhodamine B. They reported that adsorbent dosage plays a key role in dye removal efficiency as they observed a significant increment in dye removal efficiency with adsorbent dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al [31] fabricated TiO2 loaded silicalite-1 for degradation of rhodamine B. They reported that adsorbent dosage plays a key role in dye removal efficiency as they observed a significant increment in dye removal efficiency with adsorbent dosage.…”
Section: Introductionmentioning
confidence: 99%